2018
DOI: 10.1371/journal.pone.0196841
|View full text |Cite|
|
Sign up to set email alerts
|

Can excreted thiocyanate be used to detect cyanide exposure in live reef fish?

Abstract: Cyanide fishing, where a solution of sodium or potassium cyanide is used to stun reef fish for easy capture for the marine aquarium and live fish food trades, continues to be pervasive despite being illegal in many countries and destructive to coral reef ecosystems. Currently, there is no easy, reliable and universally accepted method to detect if a fish has been exposed to cyanide during the capture process. A promising non-invasive technique for detecting thiocyanate ions, the metabolic byproduct excreted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…() and has been called into question by Breen et al . (). Nevertheless, the issue of cyanide fishing is one that the legal and legitimate trade is determined to address.…”
Section: What Challenges Does the Ornamental Aquatic Industry Face?mentioning
confidence: 99%
See 1 more Smart Citation
“…() and has been called into question by Breen et al . (). Nevertheless, the issue of cyanide fishing is one that the legal and legitimate trade is determined to address.…”
Section: What Challenges Does the Ornamental Aquatic Industry Face?mentioning
confidence: 99%
“…Most recently, the test methodology described by Vaz et al (2012) could not be repeated in the field by Herz et al (2016) and has been called into question by Breen et al (2018). Nevertheless, the issue of cyanide fishing is one that the legal and legitimate trade is determined to address.…”
Section: Tackling Destructive Fishing Practices/overexploitationmentioning
confidence: 99%
“…While development of such a test has long been the goal of anti-CN fishing proponents, no test meeting the aforementioned criteria has proven viable for routine use (Breen et al, 2018). A more systematic approach to solving this long-standing problem would be to first investigate the toxicokinetics of CN absorption and its subsequent detoxification and elimination in a variety of marine fish.…”
Section: Introductionmentioning
confidence: 99%
“…The same group used this technique to monitor the MAT in the EU for the presence of cyanide fishing in the exporting countries ( Vaz, Esteves & Calado, 2017 ). The hope was that this technique could serve as a test for CN exposure in marine fish, but in the nine years that have passed since it was first reported, it has never been replicated by any other lab even though multiple laboratories have attempted to do so ( Breen et al, 2018 ; Herz et al, 2016 ; reviewed by Murray et al, 2020 ). Breen et al (2018) demonstrated by using a mass balance calculation that the SCN concentrations reported by Vaz et al (2012) and the concomitant dose of CN that the fish would have had to receive given the reported SCN concentrations were an order of magnitude higher than all known LD50s for CN in vertebrate species.…”
Section: Introductionmentioning
confidence: 99%